THE EFFECTS OF ICT INTEGRATED LEARNING ON MOTIVATION AND SELF-EFFICACY TO LEARN BIOLOGY - Ghalib BADARNE (Moldova State University, 2019)
The following article focuses on the effects of ICT integrated learning on motivation and self-efficacy to learn biology. Implementation of ICT in biology classes offers a lot of opportunities for teaching-learning process, and through pedagogical experiment was researched the opinion of students regarding the influence of ICT lessons in biology on their motivation, self-efficacy, meaningful learning and the opinion about the implementation of ICT in biology learning.   EFECTELE ÎNVĂȚĂRII PRIN INTEGRAREA MIJLOACELOR TIC ASUPRA MOTIVAȚIEI ȘI AUTOEFICACITĂȚII DE A ÎNVĂȚA BIOLOGIA În articol sunt abordate efectele învățării integrate TIC asupra motivației și autoeficacității de a învăța biologia. Implementarea TIC în clasele de biologie oferă numeroase oportunități pentru procesul de predare-învățare. Prin experimentul pedagogic a fost studiată opinia elevilor cu privire la influența lecțiilor TIC în biologie asupra motivației, eficacității lor, învățării semnificative, precum și opinia despre necesitatea implementarii TIC pentru studierea biologiei.